5 Years Follow-up of Tak Protocol in Stone Recurrence/Regrowth after Kidney Stones Removal - Konkaew, Ekkapong; Subcharoenwai, Mutita; Olankitcharoen, Kittisak (Asian Health, Science and Technology Reports, 2020)
Kidney stone is a risk factor for chronic kidney disease. Nephrocalcinosis or renal crystal deposition can lead to progressive loss of GFR that increase rate of complication and hospitalization. This research aims to evaluate 5-years follow-up of Tak Protocol in stone recurrence/regrowth, complication, hospitalization and reintervention after stone removal, compare with patients who loss follow-up. A retrospective cohort study of 106 patients with renal stone who after stone removal intervention were enrolled. All patients were divided in two groups. The protocol group (N = 70) was defined in patients who following up consistently through 5 years, and the loss follow-up group (N=36) serving as controls. Plain films KUB were used to detect stone recurrence and regrowth through 5-years follow-up. Complication, hospitalization and reintervention were reviewed from electronic medical recording database. 106 patients complete 5-years follow-up observation period. The average ages were 53.6 and 48.4 years for the protocol and loss follow-up groups, respectively. Most of 28 patients (40.0%) of protocol and 16 patients (44.4%) of loss follow-up were hypertension, whereas 25 patients (35.7%) and 15 patient (41.7%) were no underlying disease. In the stone free group, 90.5% of protocol group and 9.5% of loss follow-up group were still stone free at 60 months. In comparison with loss follow-up, stone free rate was 8.88(95%CI; 2.33-33.88, p<0.001) in protocol group. As a results of the residual stone group, protocol were 7.33(95%CI; 1.06-50.60, p=0.006) in stone free rate. Stone recurrence/size increased was found in 9.5% and 84.6% of protocol and loss follow-up group, while the result of stone size unchanged/decreased was no significant different in statistic. The recurrence and regrowth rates at one, two, three, four and five years were 2.39, 1.23, 0.84, 0.98 and 0.54 per 1,000 patient-months in the protocol group and were 7.11, 14.84, 6.57, 1.22 and 6.61 per 1,000 patient-months in the loss follow-up group, the IRR was 2.97 in the first year after intervention. The stone recurrence and regrowth were found in five years follow-up. Loss follow-up group was a higher rate than Tak protocol group. In conclusion, patient who has history of stone removal should be encouraged for lifestyle modification and made the appointment for following up at least 5 years. This protocol was shown the benefit in reducing complication and hospitalization rate.